Organizational culture and work performance: a study of TMpoint organization / Ainun Fadzilah Mohamed Saaid - Mohamed Saaid, Ainun Fadzilah (Faculty of Business and Management, 2008)
Organizational culture (henceforth referred to as OC) expresses to what extent the members of organization are willing to support each other and also the goals and development of their organization. Previous research has shown that OC has a considerable influence on employees' behavior and work results. The aim of the research is to explore the relationships between the OC estimations and work performance. The OC estimations involves in this study are 1) Artifacts, 2) Espoused Values and 3) Basic Assumptions. The purpose of this paper is to explore the relationship of organizational culture on work performance in telecommunication organizations, with special reference to TMpoint, a subsidiary company of Telekom Malaysia Berhad. This research is to seek information on the components of Organizational Culture using Edgar Schein's framework of organizational culture to determine whether it can be a bridge in measuring work performance. The study intends to provide a preliminary understanding on employees (Customer Service Representatives, CSR) behavior at TMpoint organizations. It attempts to relate the CSR behavior such as their appreciation on the artifacts, espoused values within the employees oneself, and their basic assumptions as an employee at TMpoint.